Analisis Kualitas Pelayanan Di Rsud Wangaya Kota Denpasar Dalam Perspektif E-Government (Studi Kasus Aplikasi Daftar Online Rsud Wangaya/ APDOL) - Yudistira, Putu Giri; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
This study aims to analyze the quality of e-government services in Wangaya Hospital, Denpasar City, but there are still some obstacles in its application. We use qualitative descriptive research and case study research. The data source has primary and secondary data. The purpose of this study is to find out what measures Wangaya Hospital in Denpasar City has taken to maximize information technology-based services and public services. Data collection techniques used are interviews, documentation, and observations. Data analysis techniques are data reduction, data presentation, and inference. The problem with this study is manifested in his patient complaints regarding the performance, function, and characteristics of APDOL. The theory used is egovernment with a service quality measurement method called egovqual. Pursuant to Presidential Decree No. 3/2003 and Law No. 25/2009 on Public Services. Keywords: Service Quality, E-Government, APDOL